Cristalização e relaxação em vidros óxidos uma tentativa de solução do Paradoxo de Kauzmann - Passos, Rodrigo Cardoso dos (2021)
The quest for a solution to Kauzmann’s Paradox has been a lifelong journey for many glass scientists over the last seventy years. The idea that this paradox may violate the Third Law of Thermodynamics is what makes it such an exciting topic for study, even more so, with some possible solutions proposed on the literature. The aim of this work is to find a possible solution to the paradox formulated by Kauzmann in his 1948 paper by using his very same hypothesis. If Kauzmann’s extrapolations of entropy were correct, then a supercooled liquid would have the same entropy as the stable isochemical crystalline phase at some temperature below the laboratory glass transition temperature, Tg, known as Kauzmann’s temperature, TK. If we extrapolate the liquid’s entropy even further, it becomes zero at a temperature above zero Kelvin, which violates the Third Law constituting a paradox. By comparing the relaxation kinetics with crystallization rates, both extrapolated down to TK, if the crystallization kinetics are faster than the relaxation kinetics there is no liquid at Kauzmann’s temperature, which would deny the paradox. In this case, the liquid stability limit or kinetic spinodal temperature should be higher than TK. We tested two fragile glass-forming liquids (diopside and wollastonite) and two strong liquids (silica and germania). For the fragile substances, Tks >> TK, so a supercooled liquid cannot exist at TK, and the entropy crisis is averted. On the other hand, the results for the strong liquids were inconclusive. We hope these findings entice glass researchers to further investigate the crystallization and relaxation dynamics of different strong glassforming systems at deep supercoolings.